Odpowiedzi

2010-03-16T19:46:04+01:00
Jedna trzecia x - 2 = x + 2
-2/3x=4
x=-6

1 - sześć siódmych x = cztery siódme
-6/7x=4/7-1
-6/7x=-3/7
x=1/2

6( jedna czwarta x - 2 ) = 18
6/4x-12=18
3/2x=30
x=20
2010-03-16T19:47:36+01:00
A) x+2 (1/3)=(1/3)
x=1/3 - 2(1-3)
x= -(1/3)

b) 6-x=2(3/4)
-x=2(3/4)-6
-x=-(13/4)
x= 13/4
x=3 1/4 - trzy i jedna czwarta

c) x+2,8=4,2
x= 1,4

d)x+3(1/3)=6
x+1=6
x=5

e)4,5+x=7,2
x= 2,7
Najlepsza Odpowiedź!
2010-03-16T19:49:46+01:00
A) x+2 1/3=1/3
x=1/3-2 1/3
x=-2
b)6-x=2 3/4
6-2 3/4=x
4 3/4=x
c)x+2,8=4,2
x=4,2-2,8
x=1,6
d)x+3 1/3=6
x=6-3 1/3
x= 3 1/3
e)4,5+x=7,2
x=7,2-4,5
x=2,7
1 5 1